Análisis de la migración internacional de retorno y sus remesas en Brasil, con información del Censo de Población de Brasil de 2000 - Braz Golgher, André (El Colegio de México A.C., 2009)
Nowadays millions of Brazilians live abroad; many send remittances to friends and relatives in Brazil. A sizable proportion of these individuals do return after a period abroad and they tend to return to somewhere close to or specifically to their origin. Most international migrants from Brazil return from just a few countries (Paraguay, United States and Japan) and the destiny of these flows are highly localized, and the same may occur with the remittances sent. We could not apprehend effectively this type of transfers from other types of earnings using the 2000 Brazilian Demographic Census data.